2010
DOI: 10.1002/ejoc.201001254
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Synthesis of Diarylmethanols from Aryl Bromides and Aldehydes by Using Organolithium Reagents

Abstract: A general method has been developed for preparing enantioenriched secondary alcohols by starting from aryl bromides and aldehydes. Aryl bromides were first treated with BuLi, and the resulting aryllithium reagents were mixed with titanium tetraisopropoxide and magnesium bromide. The reac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Similarly, products from the Re-face or the Si-face addition of Zn-phenylacetylide 72,73 or AlEt 3 17 reagents have been obtained using the catalysts of (R)-or (S)-BINOL derivatives (entries 8-11), respectively. The same phenomena have also been observed for the aryl addition of p-tolylLi, 34 AlPh 3 (THF), 24,27 or AlPhEt 2 (THF) 28 to benzaldehyde or 2-methylbenzaldehyde (entries [13][14][15]. This study shows that addition reactions of RTi(O-i-Pr) 3 produced desired products having the same stereochemistry (entries [15][16][17].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, products from the Re-face or the Si-face addition of Zn-phenylacetylide 72,73 or AlEt 3 17 reagents have been obtained using the catalysts of (R)-or (S)-BINOL derivatives (entries 8-11), respectively. The same phenomena have also been observed for the aryl addition of p-tolylLi, 34 AlPh 3 (THF), 24,27 or AlPhEt 2 (THF) 28 to benzaldehyde or 2-methylbenzaldehyde (entries [13][14][15]. This study shows that addition reactions of RTi(O-i-Pr) 3 produced desired products having the same stereochemistry (entries [15][16][17].…”
Section: Resultssupporting
confidence: 75%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Recent studies have shown that organoaluminum compounds are effective reagents, [17][18][19][20][21][22][23][24][25][26][27][28][29] and addition reactions can even be completed in 10 min. 24 Grignard [30][31][32][33] and lithium 34 reagents have also been established recently as efficient nucleophiles for addition reactions despite their high reactivity. In these studies, a presence of diamine additive and/or excessive amounts of Ti(O-i-Pr) 4 were used to deactivate the high reactivity of the Grignard and lithium reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the reaction conditions optimized for aryl Grignard reagents to aryllithium reagents results in the poor enantioselectivity of the arylation products. However, high enantioselectivity can be achieved when the arylation of aldehydes is carried out with a mixed reagent of an aryllithium (1.5 equiv), Ti(O i Pr) 4 (2.5 equiv), and MgBr 2 (1.5 equiv) in the presence of DPP‐H 8 ‐BINOL (2 mol %) 23c,25…”
Section: Catalytic Enantioselective Alkylation and Arylation Of Aldehmentioning
confidence: 99%
“…To solve this problem, Weber and Seebach removed the Lewis acid by centrifugation to obtain salt‐free ArTi(Oi‐Pr) 3 reagents . Harada and coworkers chose to introduce excessive ArTi(Oi‐Pr) 3 reagents derived in situ from aryllithium reagents or Grignard reagents with Ti(Oi‐Pr) 4 for a very long period of time, or to change the solvent during the reaction process . While all these measures have produced significant effects on achieving high enantioselectivities, their practicalities are greatly hampered by the great operational inconvenience and lower cost‐effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] Meanwhile, other active aryl metals such as arylaluminum, arylmagnesium, and aryllithium have transferred aryl to less active aryl titanium intermediates ArTi(Oi-Pr) 3 as nucleophiles for enantiopure diarylmethanols because of their higher reactivity. [31][32][33][34][35][36][37][38][39][40] But the enantioselectivity is still not very satisfied using only the less active ArTi(Oi-Pr) 3 in situ-generated from aryl metals and Ti(Oi-Pr) 4 to arylate aldehydes in the presence of chiral catalysts. The reason is that Lewis acids simultaneously generate in the transmetallation process and then promote the unwanted racemic background reactions and thus lead to low enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%